Evaluation of the effect of sertraline on periodontal tissues in Wistar Rats with induced periodontitis (Research, Society and Development, 2021)
Oral health is associated with systemic diseases due to the presence of microorganisms and, depression is one of the systemic pathologies and one of the drugs for treatment is sertraline. This study aims to evaluate the effects of sertraline in periodontal tissues with rats induced to ligation periodontitis. 40 adult male rats were used, divided into 4 groups, control group (CG), group with periodontal disease, (GDP), sertraline group (GS) and periodontal disease and sertraline group (GDPS). The groups with periodontal disease received a bandage around the first molars for a period of 30 days, disease induction occurred with the anesthetized animals and the aid of a modified clamp, explorer probe, adding cotton thread number 40 around the lower first molar of both sides. In the animals groups GS and GDPS,  doses of 5 mg / kg were administered, the animals groups GDP and GC received 1 mL / kg of saline solution, assessing consumption during this period. After a period, the animals were euthanized, with the hemi-mandibles removed and submitted to histological, morphological and radiographic analysis. The results, analyzed by the GraphPad Program, showed that GDP and GDPS animals did not show a statistically significant difference between them (p> 0.05), however they were significantly different from the other groups that did not induce periodontal disease (p